Analisis Ketersediaan Sumber Daya Manusia dalam Kebutuhan Industri Penyiaran Digital Studi Kasus MMTC Yogyakarta - Wayuanto , Eko; Kundori, Kundori; DTW, Joehanto; Heriyanto, Heriyanto (Asosiasi Ide Bahasa Kepri, 2025)
This study discusses the use of Artificial Intelligence (AI) technology in the production process of non-news broadcast programs at the Public Broadcasting Institution (LPP) TVRI Yogyakarta. Using qualitative methods, this study emphasizes descriptive analysis based on in-depth observations of the implementation of AI in broadcast production. The results of the study indicate that the application of AI contributes to increased efficiency and creativity, especially in scriptwriting and music creation. AI allows the production team to create more original content and reduce the risk of copyright infringement. Despite providing significant benefits, the implementation of AI is still limited due to resource constraints, data input accuracy, and lack of technical training. Driving factors such as central policies and ease of production also support the adoption of this technology. Overall, AI has positive prospects at TVRI Yogyakarta, but requires further development to be optimal in broadcast production.